The golden carpet - Massari, Alida (a, 2013)
The Golden Carpet is a Persian fairy tale about a young prince who embarks on a quest to find a magical golden carpet that can heal his ailing father, the king. Along the way, the prince faces challenges and tests of courage, ultimately proving his worth and bringing the enchanted carpet back to save the kingdom.